Block-diagonal algebras of analytic functions on Banach spaces - Taras O. G. (Karpatsʹkì Matematičnì Publìkacìï, 2012)
In this work we consider about algebras block diagonal of analytic functions on the space $ ell_1 $ and $ell_2$ and investigate spectra of these algebras.